Spinal Cord Compression Due to Intradural Extramedullary Hematopoiesis in a Young Adult with Cooley’s Anemia - Mesiano, Taufik; Rasyid, Al; Kurniawan, Mohammad; Hidayat, Rakhmad; Pangeran, David; Lubis, Anna Mira; Saekhu, Mohamad; Gunawan, Kevin; Putri, Stefanie Karina; Rahmana, Arizari Haj; Harris, Salim (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2023)
Cooley's anemia, also known as beta thalassemia major, is an inherited multisystemic disorder characterized by skeletal and non-skeletal complications resulting from hemoglobinopathies. Extramedullary Hematopoiesis (EMH) is a complication of thalassemia major due to insufficient erythropoiesis expansion. The incidence rate of paraspinal EMH in beta-thalassemia is rare but tends to be on the rise. We present a case of spinal cord compression due to intradural EMH in a 21-year-old man with Beta Thalassemia major, who exhibited acute lower motor, sensory, and autonomic disorder, along with severe anemia, and electrolyte imbalance. Patients were treated with corticosteroids, blood transfusions, electrolyte correction and pain medications. Several days later, the patient experienced clinical improvement in reduced pain and motor improvement. The patient was planned to undergo elective surgery and radiotherapy after reaching the stabilized condition. Management options of spinal cord compression due to EMH include corticosteroids, adequate blood transfusion, hydroxyurea, radiotherapy, surgical decompression, exchange transfusion, or a combination of these approaches. The choice of therapy should be based on the patient's clinical condition, diagnostic evaluations, and the size of the mass exerting pressure on the spinal cord. The optimal management of EMH remains uncertain. We need further research to establish effective treatment strategies of spinal cord compression due to EMH in Cooley’s Anemia.